Strategi Pengelolaan Madrasah dalam Meningkatkan Mutu Pendidikan Islam di Yayasan Perguruan Istiqomah Islamic Full Day School Sri Gunting - Fahri Richki; Kamil Kamil; Hadi Saputra Panggabean (Medan Resource Center, 2026)
This study examines the management strategies implemented by madrasahs in improving the quality of Islamic education at the Istiqomah Islamic Full Day School Sri Gunting Foundation. The research addresses how madrasah management policies, programs, and innovations contribute to educational quality improvement and student achievement, as well as the challenges encountered during their implementation. The study employed a qualitative case study approach involving direct observation, in-depth interviews with the principal, teachers, and relevant stakeholders, alongside document analysis. The collected data were analyzed using descriptive qualitative techniques to identify patterns, strategies, and institutional practices related to educational quality enhancement. The findings reveal that effective madrasah management is reflected in structured academic planning, teacher development programs, disciplined learning supervision, curriculum integration, and the cultivation of Islamic values within the school environment. The study also identifies several challenges, including limitations in facilities, human resource management, and the adaptation to contemporary educational demands. This study concludes that adaptive and collaborative management strategies significantly contribute to strengthening the quality of Islamic education and improving student learning outcomes in madrasah-based educational institutions.